2022
DOI: 10.1021/acs.jmedchem.1c02171
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of In Vivo Active Sphingosine-1-phosphate Transporter (Spns2) Inhibitors

Abstract: Sphingosine 1-phosphate (S1P) is a pleiotropic signaling molecule that interacts with five G-protein-coupled receptors (S1P1-5) to regulate cellular signaling pathways. S1P export is facilitated by Mfsd2b and spinster homologue 2 (Spns2). While mouse genetic studies suggest that Spns2 functions to maintain lymph S1P, Spns2 inhibitors are necessary to understand its biology and to learn whether Spns2 is a viable drug target. Herein, we report a structure–activity relationship study that identified the first Spn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 41 publications
(82 reference statements)
1
27
0
Order By: Relevance
“…Further, 33p was found to exert this effect at 16 h post administration in a dose-dependent manner (Figure B). These results are consistent with the phenotype that is observed with Spns2-knockout mice suggesting in vivo target engagement. , However, neither 32p nor 33p administration resulted in a significant decrease in plasma [S1P] (Figure C), which is unlike our experience with our first-generation Spns2 inhibitor, SLF1081851 . As mentioned previously, the literature regarding genetically modified, Spns2-deficient mice is contradictory on this point.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Further, 33p was found to exert this effect at 16 h post administration in a dose-dependent manner (Figure B). These results are consistent with the phenotype that is observed with Spns2-knockout mice suggesting in vivo target engagement. , However, neither 32p nor 33p administration resulted in a significant decrease in plasma [S1P] (Figure C), which is unlike our experience with our first-generation Spns2 inhibitor, SLF1081851 . As mentioned previously, the literature regarding genetically modified, Spns2-deficient mice is contradictory on this point.…”
Section: Resultssupporting
confidence: 89%
“…We initially focused our studies on the linker region of the pharmacophore . The fusion of phenyl and oxadiazole moieties produces attractive 5,6-bicyclic ring systems that enforce conformational rigidity and polarity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because our observations suggested that S1P exported via Spns2 is an initial step in the inside-out signaling of S1P in kidney perivascular cells to enhance inflammatory response, Spns2 may be a drug target candidate. To explore this idea, we used a small-molecule Spns2 inhibitor [SLF1081851 ( 50 ) and fig. S17A] that evokes dose-dependent peripheral blood lymphocytopenia and a decrease in plasma S1P in mice (fig.…”
Section: Resultsmentioning
confidence: 99%